Points of consideration on identification of the atmospheric fronts depicted on weather charts. Issue 1 (1st January 2023) - Miyamoto, Maki; Yamada, Tomohito J.
Abstract: Atmospheric fronts play an important role on the day-to-day variation of rainfall in Japan, North-western Pacific. They are defined as a discrepancy of air density and have been depicted on surface weather charts for more than 100 years by Japan Meteorological Agency (JMA). This study develops an approach to detect fronts from the charts published from 1978 to 2020 and investigates how detected fronts could be utilized. The fronts which are depicted on the charts might have a diverse physical characteristic in each age. One of factors is a difference in how to represent fronts. The difference also prevents from detecting fronts under a certain accuracy. Previous study demonstrates detecting fronts based on the color available from the charts. However, this approach is applicable for weather charts published after 2000 by JMA. This paper describes consideration points for a unified detection of fronts from the charts for 43 years in detail. Furthermore, we compare fronts detected by several methods and discuss a spatial scale in which their differences could be neglected.